(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2025)
This legal-procedural study addresses the motivation of jurisdictional resolutions, considering it an unavoidable guarantee of effective judicial protection against the arbitrariness of public powers. Its primary objective is to determine the exact scope of this constitutional duty, examining its functional and material dimensions. It is developed through a method of dogmatic exegesis and rigorous review of the doctrine and jurisprudential of the Spanish Constitutional Court. The argumentation reveals the double requirement of motivation, both concerning quaestio facti – justification of evidence assessment – and quaestio iuris – explicit explanation of the applied legal criteria –, highlighting the need for reinforced reasoning in cases affecting fundamental rights, minors, or gender violence. It is concluded that the adequate justification of the exercise of decisional power is essential for the system’s legitimacy, and its absence or arbitrary insufficiency constitutes a serious procedural pathology that inevitably leads to judicial nullity.